2001
DOI: 10.1093/milmed/166.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Feminine Hygiene Practices of Military Women in Deployed and Noncombat Environments

Abstract: There is limited information on how military women manage feminine hygiene practices in combat and noncombat environments. The purpose of this study was to describe feminine hygiene practices of military women in deployed and noncombat (normal) environments. A nonexperimental descriptive research design was used. The study used a survey questionnaire, the Deployed Female Health Practice Questionnaire, which was developed specifically for military women to report their experiences with hygiene issues. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…27 Among women in the U.S. military, 21% reported douching; the principal motive was cleanliness. 28 In a 1997 telephone survey from the southeastern United States, 75% of women reported ever douching, and 42% currently douched. 29 In the 1995 National Survey of Family Growth, 27% of women of reproductive age (15-44 years) douched regularly 30 ("regularly" was defined as per interviewees' judgment) compared with 37% in 1988.…”
Section: Who Douches?mentioning
confidence: 99%
“…27 Among women in the U.S. military, 21% reported douching; the principal motive was cleanliness. 28 In a 1997 telephone survey from the southeastern United States, 75% of women reported ever douching, and 42% currently douched. 29 In the 1995 National Survey of Family Growth, 27% of women of reproductive age (15-44 years) douched regularly 30 ("regularly" was defined as per interviewees' judgment) compared with 37% in 1988.…”
Section: Who Douches?mentioning
confidence: 99%
“…If the couple has never conceived despite cohabitation and exposure to pregnancy for a period of two years, it is called primary infertility, primary infertility is also referred to as primary infertility. If a couple fails to conceive following a previous pregnancy, despite cohabitation and exposure to pregnancy (in the absence of contraception, breastfeeding or postpartum amenorrhea) for a period of two years, it is secondary infertility; this is also known as secondary infertility 1 . It has been established that primary infertility is more common than secondary infertility in resource-rich countries but that the reverse is true in resource-poor countries.…”
Section: Introductionmentioning
confidence: 99%
“…Preventive medicine and food safety professionals have identified the need for an effective strategy to reduce illnesses under waterless environments within the U.S. military (Czerwinski, et al, 2001;Fein, Lin, & Levy, 1995). A previous study conducted with military personnel, found that a Purell® instant hand sanitizer regimen helped to reduce healthcare encounters by 39% (p < 0.01), respiratory illness by 40% (p < 0.01), gastrointestinal illnesses by 48% (p < 0.02), and lost training time by 44% (p < 0.01) (Mott et al, 2007).…”
Section: Justificationmentioning
confidence: 99%